Optimized Supercritical CO2 Extraction Enhances the Recovery of Valuable Lipophilic Antioxidants and Other Constituents from Dual-Purpose Hop (Humulus lupulus L.) Variety Ella - Nóra Emilia Nagybákay; Michail Syrpas; Vaiva Vilimaitė; Laura Tamkutė; Audrius Pukalskas; Petras Rimantas Venskutonis; Vaida Kitrytė (MDPI AG, 2021)
The article presents the optimization of supercritical CO2 extraction (SFE-CO2) parameters using response surface methodology (RSM) with central composite design (CCD) in order to produce single variety hop (cv. Ella) extracts with high yield and strong in vitro antioxidant properties. Optimized SFE-CO2 (37 MPa, 43 °C, 80 min) yielded 26.3 g/100 g pellets of lipophilic fraction. This extract was rich in biologically active α- and β-bitter acids (522.8 and 345.0 mg/g extract, respectively), and exerted 1481 mg TE/g extract in vitro oxygen radical absorbance capacity (ORAC). Up to ~3-fold higher extraction yield, antioxidant recovery (389.8 mg TE/g pellets) and exhaustive bitter acid extraction (228.4 mg/g pellets) were achieved under the significantly shorter time compared to the commercially used one-stage SFE-CO2 at 10-15 MPa and 40 °C. Total carotenoid and chlorophyll content was negligible, amounting to <0.04% of the total extract mass. Fruity, herbal, spicy and woody odor of extracts could be attributed to the major identified volatiles, namely β-pinene, β-myrcene, β-humulene, α-humulene, α-selinene and methyl-4-decenoate. Rich in valuable bioactive constituents and flavor compounds, cv. Ella hop SFE-CO2 extracts could find multipurpose applications in food, pharmaceutical, nutraceutical and cosmetics industries.